Excellency in banking services - A new road map for banks in the emerging new competition - Uppal, R. K. (Journal of Economics and Behavioral Studies, 2011)
The widening gap between desirability and availability is becoming a major cause of dissatisfaction in the banking industry. The bridging of this gap is one of the solutions to make the customers delight. The present study analyzes the widening gap between desirability and availability regarding reliability, accuracy, confidentiality, flexibility, e-channels, high attention to customers, low service charges and overall satisfaction of customers in three bank groups i.e. public sector banks, Indian private sector banks and foreign banks. The survey was conducted in Chandigarh in the month of October, 2008. Three banks have been selected one each from three bank groups; PNB from public sector banks, HDFC bank from Indian Private Sector banks and Amro bank from foreign banks have been taken for consideration. On the basis of five point Likert type scale, survey concludes that desirability regarding all the parameters is very high as compared to availability of banking services and on the basis of this empirical survey, study recommends some measures to bridge this gap between the D/A of service quality parameters in the banking sector in the emerging competition.